Comparing European workers. Part B, - Brady, David, 1972-; Keister, Lisa A., 1968- (Research in the sociology of work ;, 2011)
This second of two companion volumes places the labor markets, workplaces, jobs and workers of Europe in comparative perspective. It focuses on the politics, economics, sociology, and history of work and workers in Europe. It contains both qualitative and quantitative studies as well as explicitly theoretical work, and compares contemporary patterns and the recent history of European workers with other models of work worldwide. Authors contribute a variety of methodological and theoretical perspectives, with papers that push the boundaries of evidence and argument. Specific topics in 'Comparing European Workers Volume 2: Policies and Institutions' include: the political economy of active social policy in postindustrial democracies; social protection dualism, deindustrialization and cost containment; organized labor in Europe; and unionization in East European ex-communist countries. It asks such questions as 'does European-style welfare generosity discourage single mother employment?', 'whose interests do unions represent?' and 'are trade unions still redistributive?'.